Interaction specificity between the chaperone and proteolytic components of the cyanobacterial Clp protease - Tryggvesson, Anders; Mogk, Axel (Biochemical journal, 2012)
The Clp protease is conserved among eubacteria and most eukaryotes, and uses ATP to drive protein substrate unfolding and translocation into a chamber of sequestered proteolytic active sites. In plant chloroplasts and cyanobacteria, the essential constitutive Clp protease consists of the Hsp100/ClpC chaperone partnering a proteolytic core of catalytic ClpP and noncatalytic ClpR subunits. In the present study, we have examined putative determinants conferring the highly specific association between ClpC and the ClpP3/R core from the model cyanobacterium Synechococcus elongatus. Two conserved sequences in the N-terminus of ClpR (tyrosine and proline motifs) and one in the N-terminus of ClpP3 (MPIG motif) were identified as being crucial for the ClpC-ClpP3/R association. These N-terminal domains also influence the stability of the ClpP3/R core complex itself. A unique C-terminal sequence was also found in plant and cyanobacterial ClpC orthologues just downstream of the P-loop region previously shown in Escherichia coli to be important for Hsp100 association to ClpP. This R motif in Synechococcus ClpC confers specificity for the ClpP3/R core and prevents association with E. coli ClpP; its removal from ClpC reverses this core specificity.